A survey of wireless sensor network security and routing techniques - Anwar, Raja Waseem (Maxwell Science Publications, 2015)
The main purpose of the study is to review the evolution of wireless sensor network security and routing techniques. Recent years have seen tremendous growth in Wireless Sensor Networks (WSNs). As WSN's become more and more crucial to everyday life, their security and trust become a primary concern. However because of the nature of WSNs, security design can be challenging. Trust-aware routing protocols play a vital role in security of Wireless Sensor Networks (WSNs). The review study provides an overview of Wireless Sensor Network (WSN) and discusses security issues and the routing techniques for high quality of service and efficient performance in a WSN. In order to identify gaps and propose research directions in WSN security and routing techniques, the study surveys the existing body of literature in this area. The main focus is on trust concepts and trust based approaches for wireless sensor networks. The study also highlights the difference between trust and security in the context of WSNs. The trust and security are interchangeable with each other when we elaborate a secure system and not same. Various surveys conducted about trust and reputation systems in ad hoc and sensor networks are studied and compared. Finally we summarize the different trust aware routing schemes.